Modeling the impact of the River Information Services Directive on the Performance of inland navigation in the ARA Rhine Region - Verberght, Edwin; Rashed, Yasmine; van Hassel, Edwin; Vanelslander, Thierry (European Journal of Transport and Infrastructure Research, 2022)
River Information Services (RIS) are harmonized digital services that support safety, transport and traffic management in the inland navigation. RIS refer mainly to four key technologies such as Vessel Tracking and Tracing (VTT) with onboard Inland Automatic Identification System transponders (Inland AIS), Electronic Reporting International (ERI), Notices to Skipper (NtS) and Inland Electronic Chart Display and Information System (Inland ECDIS). These key technologies were developed during the nineties and received in Europe a regulatory framework through the Directive EC/2005/44 (the RIS-Directive). In 2009, most EU Member States had implemented the Directive. One of the claimed benefits of the implementation of RIS relates to a growing performance of inland navigation. In this paper, the impact of RIS on the performance of inland navigation is analyzed via a structural break cointegration approach, followed by an Error Correction Model (ECM) estimation. The empirical analysis shows that the performance of the dry bulk market is highly dynamic, while the liquid bulk market is moderately responsive to shocks. The structural break analysis could not capture any effect of the Directive on the performance of both markets, which can be attributed to several factors, such as the difficulty to isolate the policy impact, other drivers of variation, interferences of other policies and changes at the demand side.